Financial Literacy Among Generation Z: Relationship Between Knowledge, Skills, Attitudes, And Behavior (Case Study Of Students Of The Faculty Of Economics University Sarjanawiyata Tamansiswa Yogyakarta) - Fransiska Jesika Najong; Ratih Kusumawardhani; Johannes Maysan Damanika (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
This study aims to determine the level of financial literacy among generation Z and to test the correlation of financial knowledge, financial attitudes, and financial skills with their financial behavior. This study was conducted on students of the Faculty of Economics, Sarjanawiyata University, Tamansiswa. This study uses a quantitative research method. The data source used is primary data by distributing questionnaires via Google Form to respondents. The analysis method used is SEM-PLS, with a sample size of 120 respondents. The sampling technique uses the Slovin formula. This study shows that (X1) financial knowledge has no effect on financial behavior, (X2) financial skills have no effect on financial behavior and (X3) financial attitudes have an effect on financial behavior variables.